2018
DOI: 10.1016/j.postharvbio.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Within-plant variability in blueberry (Vaccinium corymbosum L.): maturity at harvest and position within the canopy influence fruit firmness at harvest and postharvest

Abstract: Està subjecte a una llicència de Reconeixement-NoComercial-SenseObraDerivada 4.0 de Creative Commons 1 Within-plant variability in blueberry (Vaccinium corymbosum L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
2
25
0
1
Order By: Relevance
“…Intriguingly, we did not find any differences in fruit firmness metrics associated with either harvest timepoint. A previous study examined the metrics between blueberry fruit ripeness and canopy position found that fruit six days post-optimal-ripeness were significantly less firm than optimally-ripe fruit [15]. While our study only evaluated ripe fruit, it is important to note that increased GDD did not impact fruit firmness metrics.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Intriguingly, we did not find any differences in fruit firmness metrics associated with either harvest timepoint. A previous study examined the metrics between blueberry fruit ripeness and canopy position found that fruit six days post-optimal-ripeness were significantly less firm than optimally-ripe fruit [15]. While our study only evaluated ripe fruit, it is important to note that increased GDD did not impact fruit firmness metrics.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, severe weather events such as spring cold spells can cause significant cold injury to low-chill and precocious blueberry cultivars, impacting yield [14]. In addition to cold-related events, yearly differences in temperature fluctuations and precipitation events, including heatwaves, drought, and flooding, affect developing fruits' quality [15,16]. Within a harvest season, weekly climate changes and increased growing degree days (GDD) can impact blueberry fruit maturation rates between sequential harvests within the same plant; exemplified by the and cause observed variation in phenolic, acid, and total soluble solid composition between harvests [17].…”
Section: Introductionmentioning
confidence: 99%
“…A great variability has been found in fruit firmness among varieties, even within the same harvest [ 8 , 9 , 10 ]. Different factors have been proposed to mediate the softening rate in blueberries, including maturation stage at harvest [ 11 ], water loss [ 12 ], and fruit orientation within the bunch [ 13 ], among others. Several studies have pointed out that the processes that underlie changes in blueberry firmness have been mainly related to the disassembly of cell wall components combined with an increase in cell wall-degrading enzymatic activities [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Softening of blueberries between harvest (e.g., in the Southern Hemisphere) and delivery to retail markets (e.g., in the Northern Hemisphere) has been closely related to water loss and physiological firmness loss (Paniagua et al, 2013). Although firmness can vary widely among cultivars (Cappai et al, 2018), it is commonly used to estimate perishability (postharvest potential) of a given lot (Lobos et al, 2018).…”
mentioning
confidence: 99%